Computer says 'no': On the materiality of software in organising tech work. - Bialski, Paula (Work Organisation, Labour & Globalisation, 2025)
This article examines the materiality of software in shaping the organisation of software work, with a focus on how software's technical constraints – such as bugs or legacy code – impact daily workflows, decision-making processes and power dynamics. This article argues that software actively organises labour by influencing how developers negotiate their tasks and assert power in relation to management, colleagues and clients. Drawing on two ethnographic examples, this article highlights how the material properties of software mediate tech work practices and professional identities, contributing to a deeper understanding of the social and technical dimensions of contemporary software development.